A pilot study of the modulation of sirtuins on arylamine N-acetyltransferase 1 and 2 enzymatic activity - Eneida Turiján-Espinoza; Rául Alejandro Salazar-González; Edith Elena Uresti-Rivera; Gloria Estela Hernández-Hernández; Montserrat Ortega-Juárez; Rosa Milán; Diana Portales-Pérez (Elsevier, 2018)
Arylamine N-acetyltransferase (NAT; E.C. 2.3.1.5) enzymes are responsible for the biotransformation of several arylamine and hydrazine drugs by acetylation. In this process, the acetyl group transferred to the acceptor substrate produces NAT deacetylation and, in consequence, it is susceptible of degradation. Sirtuins are protein deacetylases, dependent on nicotine adenine dinucleotide, which perform post-translational modifications on cytosolic proteins. To explore possible sirtuin participation in the enzymatic activity of arylamine NATs, the expression levels of NAT1, NAT2, SIRT1 and SIRT6 in peripheral blood mononuclear cells (PBMC) from healthy subjects were examined by flow cytometry and Western blot. The in situ activity of the sirtuins on NAT enzymatic activity was analyzed by HPLC, in the presence or absence of an agonist (resveratrol) and inhibitor (nicotinamide) of sirtuins. We detected a higher percentage of positive cells for NAT2 in comparison with NAT1, and higher numbers of SIRT1+ cells compared to SIRT6 in lymphocytes. In situ NAT2 activity in the presence of NAM inhibitors was higher than in the presence of its substrate, but not in the presence of resveratrol. In contrast, the activity of NAT1 was not affected by sirtuins. These results showed that NAT2 activity might be modified by sirtuins. KEY WORDS: Arylamine N-acetyltransferase, NAT, Sirtuins, Peripheral blood mononuclear cells, Nicotinamide, Resveratrol